"Aspartame: A review of genotoxicity data". (October 2015) - Kirkland, David; Gatehouse, David
Abstract: Aspartame is a methyl ester of a dipeptide of aspartic acid and phenylalanine. It is 200× sweeter than sucrose and is approved for use in food products in more than 90 countries around the world. Aspartame has been evaluated for genotoxic effects in microbial, cell culture and animal models, and has been subjected to a number of carcinogenicity studies. The in vitro and in vivo genotoxicity data available on aspartame are considered sufficient for a thorough evaluation. There is no evidence of induction of gene mutations in a series of bacterial mutation tests. There is some evidence of induction of chromosomal damage in vitro, but this may be an indirect consequence of cytotoxicity. The weight of evidence from in vivo bone marrow micronucleus, chromosomal aberration and Comet assays is that aspartame is not genotoxic in somatic cells in vivo . The results of germ cell assays are difficult to evaluate considering limited data available and deviations from standard protocols. The available data therefore support the conclusions of the European Food Safety Authority (EFSA) that aspartame is non-genotoxic. Highlights: Data from multiple in vitro and in vivo genotoxicity studies with aspartame have been reviewed. There is no evidence of induction of gene mutations in a series of bacterial mutation tests. Reported increases in chromosomal damage in vitro have not been confirmed in vivo . The data support EFSA's conclusion that aspartame is non-genotoxic.